“SuperWomen”: A Smart Mobile Application for Social Security focusing Threats and Supports for Women - Monalisa, Natasha Tanzila; Himi, Shinthi Tasnim; Ferdous, Nayeema; Islam, Md. Ezharul; Majumder, Anup (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Though in this modern society men and women are said to be given equal rights, having no gender discrimination, women are still considered weak and endlessly facing rape, domestic violence, eve-teasing, workplace violence, physical assault, cyberbullying even being killed. In South Asian countries, like Bangladesh, India, Pakistan there are thousands of cases regarding violence against women. The use of ICT including smartphone applications can be an aid in building awareness and support against these issues. Although several applications were developed worldwide, but not out there online for sensible use. In this paper, we aspire to present women with a technical solution by providing them a mobile application “SuperWomen” that is centered on urban and rural women of Asian countries and also available online. Not only women, but its voice-controlled siren feature is also a great help for physically challenged individuals, that works even on the lock screen. Survey feedback of this application shows that it takes care of each pre-incidental and post-incidental condition like an expert. This application provides user-friendly navigation for women with less technical knowledge. Its key features are secret button emergency SMS alert, location sharing with any social media, lawyer chatbot, pictorial self-defense techniques, etc. The effectiveness of this application has been justified through extensive literature review, application benchmark, performance evaluation, user survey, deployment in Google Play Store. We believe that this will bring a holistic resolution to safeguard suppressed women worldwide.